The Determinants of Banking Performance in Front of Financial Changes: Case of Trade Banks in Tunisia - NOUAILI, Makram Ahmed; ABAOUB, Ezzeddine; OCHI, Anis (International Journal of Economics and Financial Issues, 2015)
The banking sector in Tunisia has undergone, in the past decades, numerous structural changes which have affected the banking industry in particular and the economy as whole. This paper studies the internal and external determinants of bank performance in Tunisia during the period after financial reforms. We used regression analysis and panel data technique with the linear model of Bourke (1989) and followed the methodology employed by Demirgüç-Kunt and Huizinga (1999) and Dietrich and Wanzenried (2011) in order to address the issue. The empirical results showed that bank performance is positively related with capitalization, privatization and quotation. While, bank size, concentration index and efficiency are negatively related with performance indicators (measured by NIM, LIQ, ROA and ROE).As for the macroeconomic determinants, our analysis showed that the business cycle, measured by the growth of the GDP is supposed to be favorable to the improvement of the performance of the banks and negative relationship was found with inflation rate.Those variables have to arouse the interest of the decision-makers of economic and restructuring policies to direct their strategies and aiming corrective actions to promote the performance of banking and financial systems. Keywords: financial performance; interest margin; profitability; Tunisia; panel data JEL Classifications: G15; G21; L33